Impact of Si on the high-temperature oxidation of AlCr(Si)N coatings. (20th February 2022) - Jäger, Nikolaus; Meindlhumer, Michael; Zitek, Michal; Spor, Stefan; Hruby, Hynek; Nahif, Farwah; Julin, Jaakko; Rosenthal, Martin; Keckes, Jozef; Mitterer, Christian; Daniel, Rostislav
Highlights: AlCr(Si)N coatings with an Al/Cr ratio of 70/30 and 0, 2.5 and 5 at.% Si were deposited The oxidation behaviour up to 1460 °C was studied Coatings were analysed by advanced cross-sectional X-ray nanodiffraction The onset of oxidation was increased by the addition of Si from 1100 °C to 1260 °C Complex elemental and micro-structural variations after oxidation were characterized Abstract: The resistance of wear protective coatings against oxidation is crucial for their use at high temperatures. Here, three nanocomposite AlCr(Si)N coatings with a fixed Al/Cr atomic ratio of 70/30 and a varying Si-content of 0 at.%, 2.5 at.% and 5 at.% were analyzed by differential scanning calorimetry, thermogravimetric analysis and X-ray in order to understand the oxidation behavior depending on their Si-content. Additionally, a partially oxidized AlCrSiN coating with 5 at.% Si on a sapphire substrate was studied across the coating thickness by depth-resolved cross-sectional X-ray nanodiffraction and scanning trans-mission electron microscopy to investigate the elemental composition, morphology, phases and residual stress evolution of the oxide scale and the non-oxidized coating underneath. The results reveal enhanced oxidation properties of the AlCr(Si)N coatings with increasing Si-content, as demonstrated by a retarded onset of oxidation to higher temperatures from 1100 °C for AlCrN to 1260 °C for the Si-containing coatings and a simultaneous deceleration of the oxidation process. After annealing of the AlCrSiN sample with 5 at.% Si at an extraordinary high temperature of 1400 °C for 60 min in ambient air, three zones developed throughout the coating strongly differing in their composition and structure: (i) a dense oxide layer comprising an Al-rich and a Cr-rich zone formed at the very top, followed by (ii) a fine-grained transition zone with incomplete oxidation and (iii) a non-oxidized zone with a porous structure. The varying elemental composition of these zones is furthermore accompanied by micro-structural variations and a complex residual stress development revealed by cross-sectional X-ray nanodiffraction. The results provide a deeper understanding of the oxidation behavior of AlCr(Si)N coatings depending on their Si-content and the associated elemental, microstructural and residual stress evolution during high-temperature oxidation. Graphical abstract: Image, graphical abstract